In situ extraction/encapsulation of olive leaves antioxidants in zein for improved oxidative stability of edible oils - Carvalho, Amarilis Santos (2020)
This study presents a sustainable and cost-effective method for preserving the bioactivity of phenolic compounds in olive leaves (OLE) during their application. The extraction and nanoencapsulation of OLE were performed in a single-step process using a rotor-stator system with zein as the encapsulating agent. The nanoprecipitation step was carried out using an aqueous sodium caseinate solution, resulting in spherical particles with an average diameter of about 640 nm, as confirmed by Transmission Electron Microscopy. Thermal characterization showed that the produced nanoparticles were more thermally stable than free OLE until 250 degrees C, and FTIR spectra indicated effective interaction between the phenolic compounds and zein. Antioxidant activity was evaluated using TBARS, DPPH, ABTS, and FRAP assays, with results showing that encapsulated OLE had lower antioxidant activity than free OLE. The best antioxidant capacity results were determined by TBARS assay, with IC50 results equal to 43 and 103 & mu;gOLE/mL for free and encapsulated OLE, respectively. No anti-inflammatory potential was detected for both samples using the RAW 264.7 model, and only free OLE showed cytotoxic activity against lung cancer and gastric carcinoma. Encapsulated and free OLE were used as antioxidants in soy, palm, and palm kernel oils and compared to BHT using Rancimat. The Schaal Oven Test was also performed, and the PARAFAC chemometric method analyzed the UV-Vis spectra, which revealed high stability of the oil when 300 mg or the nanoparticles were added per kg oil. Results suggested that zein-encapsulated olive leaf antioxidants can improve the oxidative stability of edible oils.